Enhanced Immune Response Improves Resistance to Cadmium Stress in Triploid Crucian Carp - Liu, Wen-bin; Wang, Min-meng; Dai, Liu-ye; Dong, Sheng-hua; Yuan, Xiu-dan; Yuan, Shu-li; Tang, Yi; Liu, Jin-hui; Peng, Liang-yue; Xiao, Ya-mei (Frontiers in Physiology, 2021)
Previous research has indicated that triploid crucian carp (3n fish) have preferential resistance to cadmium (Cd) compared to Carassius auratas red var. (2n fish). In this article, comparative research is further conducted between the 2n and 3n fish in terms of the immune response to Cd-induced stress. Exposure to 9 mg/L Cd for 96 h changed the hepatic function indexes remarkably in the 2n fish, but not in the 3n fish. In the serum of Cd-treated 2n fish, the levels of alanine amino transferase, aspartate aminotransferase, adenosine deaminase, and total bilirubin significantly increased, while the levels of total protein, albumin, lysozyme, and anti-superoxide anion radicals decreased demonstrating hepatotoxicity. By analysis of transcriptome profiles, many immune-related pathways were found to be involved in the response of 3n fish to the Cd-induced stress. Expression levels of the immune genes, including the interleukin genes, tumor necrosis factor super family member genes, chemokine gene, toll-like receptor gene, and inflammatory marker cyclooxygenase 2 gene were significantly enhanced in the hepatopancreas of the Cd-treated 3n fish. In contrast, the expression levels of these genes decreased in the 2n fish. This research provides a theoretical basis for polyploid fish breeding and is helpful for the ecological restoration of water due to pollution.